AN ENQUIRY INTO THE LEASE VS BORROW DECISION OF FIRMS - Thomas Anastassiou; Angelos Tsaklanganos (European Scientific Journal, ESJ, 2014)
Greece has started to employ a new measure of financing with quite important success, especially over the last years, and this is the option of financial leasing. The measure has been decreed and put into effect quite earlier, in year 1986, (while it has been used widely long time ago in the United States and elsewhere) but only lately it has started in Greece to be considered seriously as an alternative source of investment financing. Three main issues are addressed in this paper. First, an attempt is made to answer the question whether the lease decision and the borrow decision of firms are substitutes or compliments. Assumptions about complimentarity run the risk of deciding in favour of leasing. Especially in Greece, where at the moment all leases are treated as operating, lessee firms are candidates for making the wrong assumptions about the impact of leasing in their financial position. Also in this paper another question is asked, as long as a firm has decided on the lease option, as to how many units of capital equipment of a certain type the company is optimal to employ through leasing. A decision rule is employed and an illustration of this decision rule is made. The final question which is posed is whether leasing is viewed as a financing or as an investment decision. We believe that treading leasing as a financing decision is a fundamental assumption. Firms though that decide in favour of investment projects based on favourable lease terms only, run the risk of accepting otherwise unacceptable projects and vice versa. What is suggested at present is to view at the combined result of both the investment and financing analysis in order to decide about the acceptability of an investment project.